Proposal of accuracy analysis of indoor tracking systems in basketball - José Pino-Ortega; Carlos David Gómez-Carmona; Xavier Reche; Joan Ramón Tarragó; Alejandro Bastida-Castillo (Revista da Educação Física)
The development of tracking technology caused a exponentially grow-up of research into this topic. The use of standardized methodologies is useful to contrast data of different studies. On the other hand, a low-cost reference system is needed. For this reason, the main aim of the present research is the description of a specific protocol to accuracy assessment of tracking location in indoor conditions in basketball. It can resume in three steps with detailed and easily procedures in the method section. The accuracy analysis method presented can report the centimeter of accuracy in each coordinate that the tracking system measure. A standardized protocol to evaluate the location on indoor conditions in basketball will provide to the sport science professionals a useful tool to analyze the accuracy and reliability of all tracking system, being the results can compare both within and between-court.